Welcome Aboard!:Motorboating Encounters in Arctic Inland Waters - Markuksela, Vesa (Palgrave Macmillan, 2023)
This study discusses the material and mobile encounters of human and nonhuman bodies through a water-based leisure activity practice. The focus is on recreational boating in the Lappish summer’s inland waters, where boaters likely encounter changing weather and water conditions. The study combines sociomaterial practice theory and sensory ethnographic methods. It presents boating practice as an intertwined intra-action across the elements of the boat crew, nonhuman water body and materialised weather. This transforming conglomerate is named a more-than-human assemblage of boating practices. It is a proposal for an analytical category to examine how human and nonhuman mobile bodies perform practice and what this dynamic practice does to the bodies. This study discusses the material and mobile encounters of human and nonhuman bodies through a water-based leisure activity practice. The focus is on recreational boating in the Lappish summer’s inland waters, where boaters likely encounter changing weather and water conditions. The study combines sociomaterial practice theory and sensory ethnographic methods. It presents boating practice as an intertwined intra-action across the elements of the boat crew, nonhuman water body and materialised weather. This transforming conglomerate is named a more-than-human assemblage of boating practices. It is a proposal for an analytical category to examine how human and nonhuman mobile bodies perform practice and what this dynamic practice does to the bodies.